2022
DOI: 10.1007/s11033-022-07843-x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating expression and clinical significance of LncRNA ANRIL in diabetic kidney disease

Abstract: Background Long noncoding RNA ANRIL has been found to be involved in the pathogenesis of diabetic kidney disease (DKD) and is expected to be a new target for prevention of DKD. However, the circulating expression and clinical significance of ANRIL in DKD patients is uncertain. This study aims to explore this issue. Methods The study consisted of 20 healthy controls, 22 T2DM patients (normalbuminuria) and 66 DKD patients (grouped as follows: microalbuminuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In addition to the 103 review articles, a total of 246 studies were removed for the following reasons: 120 were animal studies, 108 did not report AUC values, and 18 did not report numerical sensitivity or specificity results. In total, 24 studies ultimately met our eligibility criteria, of which T2DM, DN, and DR were analyzed in 17, 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 5, 5 , 30 , 35 , 36 , 37 and 7 studies, 4 , 28 , 29 , 32 , 37 , 38 , 39 respectively (some articles included more than one of these outcomes). Table 1 provides the specifics of the survey characteristics and summarizes the quality assessment results.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the 103 review articles, a total of 246 studies were removed for the following reasons: 120 were animal studies, 108 did not report AUC values, and 18 did not report numerical sensitivity or specificity results. In total, 24 studies ultimately met our eligibility criteria, of which T2DM, DN, and DR were analyzed in 17, 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 5, 5 , 30 , 35 , 36 , 37 and 7 studies, 4 , 28 , 29 , 32 , 37 , 38 , 39 respectively (some articles included more than one of these outcomes). Table 1 provides the specifics of the survey characteristics and summarizes the quality assessment results.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that ANRIL is upregulated in serum samples from patients with multiple malignancies, including glioma and breast cancer 15 , 16 . The higher expression of circulating ANRIL in the peripheral blood and serum of patients with diabetes and ischemic stroke has been reported 17 , 18 . As demonstrated by Holdt and Teupser 12 , atherosclerosis progression is associated with decreased expression of circular ANRIL and increased expression of linear ANRIL .…”
Section: Introductionmentioning
confidence: 90%
“…Some lncRNAs have a diagnostic role in diabetic complications. ANRIL and MALAT1 are upregulated in patients with DN, as the biomarker for the diagnosis of diabetic kidney disease ( 22 , 26 ). TINCR and HOTAIR are downregulated in serum and myocardial biopsies of patients with DCM and can be used to effectively distinguish patients with DCM from healthy controls ( 58 ; 102 ).…”
Section: Clinical Application Of Lncrnas In Diabetic Complicationsmentioning
confidence: 99%